An analysis of the landscape structure changes as an ecological approach to achieve sustainable regional planning (Case Study: Latian Dam Watershed) - Shafie, Banafsheh; Javid, Amir Hossein; Irani Behbahani, Homa; Darabi, Hassan; Hosseinzadeh Lotfi, Farhad (Journal of Environmental Engineering and Landscape Management, 2023)
The formation of modifications or conception in the landscape could possibly, be a procedure relative to its natural and non-disturbance process; and it could be hastened by the occurrence of disturbance regimes. The objective of this research is to survey the changes in a landscape structure, over a period of 30 years, to attain information, as to the current conditions of land use, utilizing landscape metrics in the watershed area of the Latian Dam, so as to analyze the results and the voids present, towards obtaining a specified sustainable regional planning for the abovementioned watershed. Land use was identified and reviewed by means of four Landsat satellite images for 1987, 1998, 2007, and 2017; and in this watershed, it was classified into four classes, (a) build-up areas, (b) vegetated areas, (c) bare lands and (d) water bodies. Subsequently, by taking advantage of 7 metrics at the landscape level and 8 metrics at the class level, the landscape structure in this watershed was quantified by utilizing the Fragstats 4.2 Software. The survey results illustrated an increment in the number of patches (NP), decrementing the mean area of the patches (AREA-MN), and increasing the Interspersion & Juxtaposition Index (IJI) signifies amplified fragmentation at the landscape level in this watershed. Similarly, the NP has also incremented at the class level, and thus, the fragmentation of patches and fragmentation in the entire three classes of land use, namely, build-up areas, bare lands, and vegetated areas has occurred. The amount of patchiness for the build-up class, with due attention to the increment in the mean area of patches (AREA-MIN), which demonstrates the fact that, this class is inclined and has a tendency towards a coarse-grained structure and a metric decrement in the AREA-MIN in the vegetated areas, illustrates that this class is prone to the fine-grained structure.